Exploring SDGs Regulatory Frameworks and Regional Regulation for Climate Change Mitigation and Adaptive Resilience in Coastal Communities - Naswar; Ilmar, Aminuddin; Mukhlis, Muhammad Mutawalli; Achmad; Md. Khalid, Rasyikah (Jurnal IUS Kajian Hukum dan Keadilan, 2024)
Climate change will cause ecosystem changes that will affect all aspects of human life on earth. The Intergovernmental Panel on Climate Change (IPCC), in its fifth assessment report (AR5), stated that climate change is also having an impact on the marine environment. Indonesia as an archipelagic country will of course also feel the domino effect of climate change. Therefore, climate change is very urgent to be discussed in Indonesia. This article will examine and formulate derivative regulations which are implementation instruments to provide legal protection for the environment and coastal residents when facing the impacts of climate change. This paper applies normative research methods as well as a contextual approach, historical approach, legal approach, comparative approach and case approach which will then be analyzed qualitatively. Specifically, this article will analyze the Buton Regency, especially the North Buton Regency government's efforts to overcome climate change which is realized by the existence of regional regulations that specifically regulate Climate Change Adaptation [API] as well as integrating regional regulations with API elements, especially in the sectors of spatial design, development planning and disaster management. So, it can be a reference for a regions that have coastal areas to achieve the target of Sustainable Development Goals [SDGs] point 13.